Granting Priority Rights and Compensation to Owners of Destroyed Land - Tri Cahya Indra Permana; Sri Wahyu Handayani; Kamilah Wati bt Mohd (Jurnal Dinamika Hukum, 2023)
Soil possesses unique properties. This is due to the fact that, on one hand, land is a non-biological resource, implying that it cannot naturally regenerate in abundance. This research aims to analyze the significance of granting priority right and compensation to owners of destroyed land. This research adopts normative legal research approach. The result of this research reveals that the Regulation of the Minister of ATR/Head of BPN Number 17 of 2021 was issued to regulate the procedure for determining the destruction of land. Nevertheless, the Supreme Court opines that Article 15 paragraph (1) of the regulation fails to uphold a sense of justice and is contrary to higher laws and regulations.Keywords: Granting Priority Rights, Compensation, Owner of Destroyed Land.